MOLECULAR DIAGNOSTIC RATIOS TO ASSESS THE APPORTIONMENT OF PETROLEUM HYDROCARBONS CONTAMINANTION IN MARINE SEDIMENT - Agung Dhamar Syakti (Universitas Jenderal Soedirman, 2016)
As maritime fulcrum nation, in Indonesia, marine environmental analytical chemistry field is still under developed. So that why, this review paper aims to provide basic understanding of the use some molecular diagnostic indices using n-alkanes indexes and polycyclic aromatic hydrocarbons (PAHs) diagnostic ratios to estimate the source of apportionment of the hydrocarbons contamination and origin. The n-alkane chromatograms were then used to characterize the predominance of petrogenic or biogenic either terrestrial or aquatic. Furthermore, characterization allowed to discriminate riverine versus marine input. The occurrence of a broad unresolved complex mixture can be an evidence of biodegraded petroleum residues. For aromatic compounds, the prevalence of petrogenic, pyrolitic, and combustion-derived can be easily plotted by using isomers ratio calculation. This paper thus provides useful information on the hydrocarbon contamination origin, especially in marine sediments. Further researches should be undertaken in order to validate the use of molecular diagnostic ratio with isotopic approach.